1990
DOI: 10.1177/019251390011004002
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Resource Policies on Employees

Abstract: Using a number of empirical studies of human resource policies in Fortune 500 companies, this article focuses on (a) the major work/family problems faced by employees, (b) how work/family programs affect productivity, (c) what trends are emerging among companies, and (d) how a subsample of leading scientific companies and universities are responding to work/family issues. The seven major issues employees face are examined: child care, elder care, work time and timing, relocation, job demands and autonomy, supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
1
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(101 citation statements)
references
References 0 publications
5
93
1
2
Order By: Relevance
“…These are not only likely to perpetuate the long hours culture in the UK but to be of continuing detriment to women. Whilst general attitudes towards an organisational culture have been shown to be important in terms of uptake of flexible working options (Galinsky & Stein, 1990;Lewis & Taylor, 1996;Thompson et al, 1999) this study has highlighted that traditional views about women, work performance and working patterns still persist. Successful career women, as demonstrated in recent studies by Jones and Gittins (2009) and Ezzedeen and Ritchey (2009) suggest this success is achieved by long hours work when necessary.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These are not only likely to perpetuate the long hours culture in the UK but to be of continuing detriment to women. Whilst general attitudes towards an organisational culture have been shown to be important in terms of uptake of flexible working options (Galinsky & Stein, 1990;Lewis & Taylor, 1996;Thompson et al, 1999) this study has highlighted that traditional views about women, work performance and working patterns still persist. Successful career women, as demonstrated in recent studies by Jones and Gittins (2009) and Ezzedeen and Ritchey (2009) suggest this success is achieved by long hours work when necessary.…”
Section: Discussionmentioning
confidence: 92%
“…Thompson, Beauvais, and Lyness (1999) and Allen (2001) found that both perceived supervisor support and perceptions of family support within the organisation were positively related to overall use of flexible working arrangements. Thompson et al, (1999) provided evidence to suggest that the type and number of work-family programmes offered is not as important as the culture of an organisation, which, in itself, is crucial for determining not only whether people will use benefits, but also their general attitudes towards the organisation (Galinsky & Stein, 1990;Lewis & Taylor, 1996;Thompson et al, 1999). Bond and Wise (2003) found that the management of family leave policies was one of the increasing number of HR practises that are devolved to line managers and that managerial discretion was often a critical part of the formal provision within an organisation.…”
Section: Introductionmentioning
confidence: 99%
“…These are not only likely to perpetuate the long hours culture in the UK but to be of continuing detriment to women. Whilst general attitudes towards an organisational culture have been shown to be important in terms of uptake of flexible working options (Galinsky & Stein, 1990;Lewis & Taylor, 1996;Thompson et al, 1999) this study has highlighted that traditional views about women, work performance and working patterns still persist. Successful career women, as demonstrated in recent studies by Jones and Gittins (2009) and Ezzedeen and Ritchey (2009) suggest this success is achieved by long hours work when necessary.…”
Section: Discussionmentioning
confidence: 89%
“…Thompson, Beauvais, and Lyness (1999) and Allen (2001) found that both perceived supervisor support and perceptions of family support within the organisation were positively related to overall use of flexible working arrangements. Thompson et al, (1999) provided evidence to suggest that the type and number of work-family programmes offered is not as important as the culture of an organisation, which, in itself, is crucial for determining not only whether people will use benefits, but also their general attitudes towards the organisation (Galinsky & Stein, 1990;Lewis & Taylor, 1996;Thompson et al, 1999). Bond and Wise (2003) found that the management of family leave policies was one of the increasing number of HR practises that are devolved to line managers and that managerial discretion was often a critical part of the formal provision within an organisation.…”
Section: Introductionmentioning
confidence: 99%
“…Galinsky and Hughes (1987) found that working parents felt having their supervisors trained to be more accommodating during family crises was one of the most advantageous ways to improve the quality of their family lives, second only to increased pay. Past research has shown that supervisor support reduces employee stress, decreases role conflict, and improves family functioning Galinsky & Stein, 1990;Greenhaus, Bedeian, & Mossholder, 1987). Supervisors' supportive behaviors, specifically family-supportive supervisor behaviors (FSSB), are being examined as a moderator of the relationship between work-family conflict and safety outcomes in that the negative work-family conflict and safety performance relationships will be weaker at higher levels of supervisor support.…”
Section: Family-supportive Supervisor Behaviors (Fssb)mentioning
confidence: 99%